2015
DOI: 10.1007/s11096-015-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Consumer knowledge and perceptions about antibiotics and upper respiratory tract infections in a community pharmacy

Abstract: This study confirms a lack of knowledge among consumers about the efficacy of antibiotics in treating viral infections despite education campaigns. The findings strongly suggest there is a need for pharmacists and other health care professionals to elicit consumer beliefs and understanding about antibiotics and to tailor their advice appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…In one Australian consumer study, over one-third of the 252 participants thought that taking antibiotics when suffering from a cold or flu would lead to more rapid recovery, while nearly one-fifth considered antibiotics as a cure for viral infections. 43 Links have been established between antibiotic use and paediatric asthma 44,45 and eczema 46 and less common but grave physical and psychoactive side effects associated with particular antibiotics. The class of antibiotics fluoroquinolones is known to cause tendonitis, central nervous system (CNS) effects, peripheral neuropathy, 47 and juvenile fluoroquinolone-induced joint/cartilage toxicity.…”
Section: Urtis and Antibioticsmentioning
confidence: 99%
“…In one Australian consumer study, over one-third of the 252 participants thought that taking antibiotics when suffering from a cold or flu would lead to more rapid recovery, while nearly one-fifth considered antibiotics as a cure for viral infections. 43 Links have been established between antibiotic use and paediatric asthma 44,45 and eczema 46 and less common but grave physical and psychoactive side effects associated with particular antibiotics. The class of antibiotics fluoroquinolones is known to cause tendonitis, central nervous system (CNS) effects, peripheral neuropathy, 47 and juvenile fluoroquinolone-induced joint/cartilage toxicity.…”
Section: Urtis and Antibioticsmentioning
confidence: 99%
“…7 From their perspective, antibiotic resistance develops not due to mutations in bacteria but the human body gradually mounting tolerance, meaning every antibiotic can only be used for a limited time period before it becomes obsolete. The above observations have been replicated in many other studies as well, [8][9][10] suggesting that we are still far from reaching an adequate understanding in the general populace, and initiatives designed to raise greater awareness in this subject area should be more extensively implemented and promoted.…”
Section: Public Perceptions Of Antibiotic Resistance: the Patient Andmentioning
confidence: 65%
“…Fredericks et al . recently identified that some consumers have a tendency to self‐diagnose and are misinformed about the efficacy of antibiotics; these traits may contribute to inappropriate antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…Despite ongoing national educational campaigns, some Australians are still confused about the appropriateness of antibiotic therapy . Inappropriate use of antibiotics promotes resistance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation